Organic Solution Advanced Spray-Dried Microparticulate/Nanoparticulate Dry Powders of Lactomorphin for Respiratory Delivery: Physicochemical Characterization, In Vitro Aerosol Dispersion, and Cellular Studies - Wafaa Alabsi; Fahad A. Al-Obeidi; Robin Polt; Heidi M. Mansour (Pharmaceutics, 2020)
The purpose of this study was to formulate Lactomorphin (MMP2200) in its pure state as spray-dried(SD) powders, and with the excipient Trehalose as co-spray-dried(co-SD) powders; for intranasal and deep lung administration with Dry Powder Inhalers (DPI). Lactomorphin is a glycopeptide which was developed for the control of moderate to severe pain. Particles were rationally designed and produced by advanced spray drying particle engineering in a closed mode from a dilute organic solution. Comprehensive physicochemical characterization using different analytical techniques was carried out to analyze the particle size, particle morphology, particle surface morphology, solid-state transitions, crystallinity/non-crystallinity, and residual water content. The particle chemical composition was confirmed using attenuated total reflectance-Fourier-transform infrared (ATR-FTIR), and Confocal Raman Microscopy (CRM) confirmed the particles’ chemical homogeneity. The solubility and Partition coefficient (LogP) of Lactomorphin were determined by the analytical and computational methodology and revealed the hydrophilicity of Lactomorphin. A thermal degradation study was performed by exposing samples of solid-state Lactomorphin to a high temperature (62 °C) combined with zero relative humidity (RH) and to a high temperature (62 °C) combined with a high RH (75%) to evaluate the stability of Lactomorphin under these two different conditions. The solid-state processed particles exhibited excellent aerosol dispersion performance with an FDA-approved human DPI device to reach lower airways. The cell viability resazurin assay showed that Lactomorphin is safe up to 1000 μg/mL on nasal epithelium cells, lung cells, endothelial, and astrocyte brain cells.